2016
DOI: 10.1186/s12879-016-1487-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Uganda II is more susceptible to rifampicin and isoniazid compared to Beijing and Delhi/CAS families

Abstract: BackgroundMycobacterium tuberculosis Uganda family is the predominant cause of tuberculosis in Uganda. Reasons for this are not clear but are likely to be due to the rampant person-to-person transmission or delayed susceptibility of the organism to drugs during treatment, which may lead to continuous shedding of infectious bacilli, among others. The objective of this study was to determine in vitro, the susceptibility patterns of M. tuberculosis Uganda family compared with Beijing and Delhi/CAS, other M. tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Geometric mean CSF concentrations were ~6-fold higher with IV-20 at 1.74 mg/L (95% CI, 1.20–2.53) and 8-fold higher with PO-35 at 2.17 mg/L (95% CI, 1.64–2.86; P < .001 for each). A CSF concentration > 1 mg/L, the rifampicin minimal inhibitory concentration (MIC) for the predominant M. tuberculosis strain in Uganda [ 29 ], occurred in 11% (2/18) with standard-of-care treatment, 93% (14/15) with IV-20, and 95% (18/19) with PO-35 ( P < .001). PK results are further described in Table 2 and Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric mean CSF concentrations were ~6-fold higher with IV-20 at 1.74 mg/L (95% CI, 1.20–2.53) and 8-fold higher with PO-35 at 2.17 mg/L (95% CI, 1.64–2.86; P < .001 for each). A CSF concentration > 1 mg/L, the rifampicin minimal inhibitory concentration (MIC) for the predominant M. tuberculosis strain in Uganda [ 29 ], occurred in 11% (2/18) with standard-of-care treatment, 93% (14/15) with IV-20, and 95% (18/19) with PO-35 ( P < .001). PK results are further described in Table 2 and Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As in many TBM trials, microbiological confirmation was only made in half the participants. Because a minority of TBM patients are culture positive, and the complexity of performing rifampicin MIC, the MIC was derived from population estimates within the same TB laboratory [ 29 , 38 ]. This phase II study was adequately powered for quantification of PK parameters, but due to limited sample size, no conclusions about clinical outcomes can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction and review were performed on 20,508 isolate entries of TB patients for DST. The NTRL is a Biosafety Level (BSL) 3 Laboratory that is fully furnished to manipulate TB cultures and specimens [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other authors reported an MIC of 0.06 μg/mL for INH and RIF against M. tuberculosis H37Rv strain (CAMACHO-CORONA et al, 2008). Similarly, low MICs of 0.05 μg/mL for INH and 0.03 μg/mL for RIF have been reported (KASULE et al, 2016).…”
Section: Discussionmentioning
confidence: 75%